Analysis of reparative osteogenesis at diaphysial fractures of tibia by roentgenography data - Sharmazanova, Olena; Moseliani, Khatia (ScienceRise: Medical Science, 2017)
Aim of research. To study the features of reparative osteogenesis at diaphysial tibia fractures in patients of a young and middle age. Material and methods. There was presented the analysis of x-ray photographs of 122 patients with diaphysial tibia fractures 18 - 60 years old (men - 54,2%, women - 45,8%) in sanitary projections at the dynamic observation from 8 months to 3 years. Research results. It was established that the full accretion of fractures in terms up to 4 months was detected only in 28,7% of cases (35 patients), in terms up to 6 months -in 33,6% (41 patients), up to 8 months - in 16, 4% (20 patients). In 26 patients (21,3%) the accretion of diaphysial tibia fractures was forming during 1,5-2 years. Most often at fractures accretion was observed a periosteal callus (83,6%), less often – intermediary one (11,4%) and paraossale (4,9%). Complication at fractures accretion were detected in 46 (37,7%) of traumatized persons. Conclusions. In most cases diaphysial fractures of tibia accreted longer than 4 months with complications in each third patient